Cultura corporal e tempo livre em áreas de reforma agrária: notas acerca da educação escolar e da emancipação humana - Tiago Nicola Lavoura (2013)
The present study lies in the problematic field of work, education and leisure and has as its object the corporal culture and school education in social practice of MST. From the following investigative problem: "What the contents and the fundamentals of the corporal culture within the leisure, their connections, relationships and contradictions with work and education, training possibilities and perspectives on emancipatory Pedagogical Political Projects in educational and cultural areas agrarian reform?", defended the thesis that there are structural elements of the corporal culture within the leisure which are ultimately determined by the mode of production of country life as well as in defense of the mediation of school and school work in the appropriation of a body of knowledge about the corporal culture which perspective with human emancipation as central to the experience of free time beyond the logic of capital. The central aim of the research was to understand the possibilities and prospects formative emancipation of the corporal culture within the leisure Pedagogical Political Projects of education and culture in agrarian reform areas of the Brazilian countryside, unfolding in the following specific objectives: a) highlight the meaning of Marxist class production mode of human existence and its constituent complexes in search of understanding of the agrarian question; b) Identify the ontological and historical determinants of leisure and its emancipatory possibilities within the framework of the bourgeois order, in particular, in the Brazilian countryside; and c) investigate the pedagogical foundations of the corporal culture in school education MST and its linkages with constituent work and free time in agrarian reform areas. With the development of research from theoretical and methodological assumptions of historical and dialectical materialism, four moments spiraled up and up crisscrossed to the completion of the thesis, which can be characterized as the instruments of thought and research: data structure and conjuncture; references and productions of knowledge, documents and structured interviews. So, we were unable to confirm the hypotheses that 1) The social function of land and its economic occupation, from the mode of production of country life and relationship of humans with the earth, ultimately determine the activities of cultural and educational sphere, among which the activities of the corporal culture within the leisure; 2) The school educational work, in its role of mediation in practice global social transmission of knowledge developed, determinations back to the fundamentals of the corporal culture within the leisure field, in particular those that express ethical-evaluative content of emancipation human and 3) chances formative and emancipatory prospects of the corporal culture within the leisure field are located in Pedagogical Political Projects of education and culture in the areas of agrarian reform, which resulted from the struggle of the peoples of the field by winning the land, its social and collective overcoming capitalist order organizing life. We conclude by stating the need for the development of the educational work of the school and the MST whole working class to be guided by the historical-critical pedagogy as a means of facilitating formation full of content - including knowledge of the corporal culture - each unique individual so that they can take advantage of all the material and immaterial productions pr oduced collectively by men, especially in their free time and leisure.